Aptamer‐PROTAC Conjugates (APCs) for Tumor‐Specific Targeting in Breast Cancer. Issue 43 (11th August 2021) - He, Shipeng; Gao, Fei; Ma, Junhui; Ma, Haoqian; Dong, Guoqiang; Sheng, Chunquan
Abstract: Development of proteolysis targeting chimeras (PROTACs) is emerging as a promising strategy for targeted protein degradation. However, the drug development using the heterobifunctional PROTAC molecules is generally limited by poor membrane permeability, low in vivo efficacy and indiscriminate distribution. Herein an aptamer‐PROTAC conjugation approach was developed as a novel strategy to improve the tumor‐specific targeting ability and in vivo antitumor potency of conventional PROTACs. As proof of concept, the first aptamer‐PROTAC conjugate (APC) was designed by conjugating a BET‐targeting PROTAC to the nucleic acid aptamer AS1411 (AS ) via a cleavable linker. Compared with the unmodified BET PROTAC, the designed molecule (APR ) showed improved tumor targeting ability in a MCF‐7 xenograft model, leading to enhanced in vivo BET degradation and antitumor potency and decreased toxicity. Thus, the APC strategy may pave the way for the design of tumor‐specific targeting PROTACs and have broad applications in the development of PROTAC‐based drugs. Abstract : The first aptamer‐PROTAC conjugate (APC) was designed to improve the tumor specific targeting and in vivo antitumor potency of conventional PROTACs. This strategy may pave the way for the design of tumor‐specific targeting PROTACs and have broad applications in PROTAC‐based drug development.